Tigers, Terrain, and Human Settlement Influence the Occupancy of Leopards (Panthera pardus) in Southwestern Tarai, Nepal - Laxmi Raj Joshi; Rabin Bahadur K. C.; Madhu Chetri; Morten Odden; Olivier Devineau; Ajay Karki; Bhagawan Raj Dahal; Naresh Subedi (Ecology and Evolution)
ABSTRACT Maintaining a healthy population of common leopards, a highly adaptive felid, requires updated information on their spatial occurrence. In Nepal's Tarai region, leopards coexist with tigers, which are well‐studied felid throughout its range. However, knowledge is very scarce on the patterns of leopard occupancy. We conducted an occupancy survey using remote cameras in southwestern Tarai, particularly in Shuklaphanta National Park, Nepal, to assess habitat use by leopards from December 2022 to January 2023. Naive and model‐averaged occupancy estimates were 0.51 and 0.6563 (SE: 0.022, 95% CI: 0.612, 0.70), respectively. The detection of leopards was negatively correlated with the presence of tigers. Leopard occupancy was higher closer to human settlement and higher in rugged terrain. At a time when Nepal has achieved its tiger conservation targets, efforts are required to maintain adequate prey biomass to minimize fatal encounters between tigers and leopards and displacement of leopards peripheral to the settlement area, where villagers might kill them in retaliation of livestock killing. Long‐term monitoring is required to improve understanding of the interaction between leopards, tigers, and humans in the Tarai region of Nepal.